Positive, negative or neutral? The “appraisal” variable in content analyses studies of the media - Steibel, Fabro; Marinkova, Milena (E-Compós, 2013)
This article interrogates the assumption that media content analyses based on mixed-method research are free of contradictions. We argue that when qualitative and quantitative methods are used simultaneously, the different research paradigms applied in the process cannot be reconciled in a bid to produce consistency. In order to do this, we review in this paper the findings and methodology of a project funded by the EU Fundamental Rights Agency on the coverage of migrants and minorities in the UK press. Focusing more specifically on the codification and interpretation of the Appraisal variable used in the project, we investigate how its subjectivedefinition and challenging quantification are indicative of some of the problems of consistency accompanying the intersection of qualitative and quantitative approaches to content analysis. In this sense, we do not dismiss the potential of mixedmethod research to deliver insightful findings, but warn against the mechanical application ofcross-paradigmatic approaches, and argue that the gaps and inconsistencies exposed by different paradigms can reveal more about the ambivalence of media representation than their uncritical synchronisation can.KeywordsMixed methods. Content analysis. Journalism. Human rights.